2018
DOI: 10.1186/s13223-018-0260-y
|View full text |Cite
|
Sign up to set email alerts
|

Common allergies in urban adolescents and their relationships with asthma control and healthcare utilization

Abstract: BackgroundUrban adolescents suffer a disproportionate burden of asthma morbidity, often in association with allergies. Literature is limited on comparing various types of allergies regarding prevalence and associations with asthma morbidity in urban dwelling adolescents. The purpose of this study was to examine the prevalence of common allergies reported by urban adolescents and to assess their relationships to healthcare utilization and asthma control.MethodsStudy participants included 313 urban adolescents (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Cockroach allergies was associated with 2.2 times as many specialist visits, while mouse allergies was associated with 1.6 times as many emergency department visits. 20 These results are similar to this study findings and this points towards doing a detailed sensitization testing for cases of poorly controlled asthma. In such cases, it may be necessary to re-consider environmental and allergen control measures.…”
Section: Discussionsupporting
confidence: 91%
“…Cockroach allergies was associated with 2.2 times as many specialist visits, while mouse allergies was associated with 1.6 times as many emergency department visits. 20 These results are similar to this study findings and this points towards doing a detailed sensitization testing for cases of poorly controlled asthma. In such cases, it may be necessary to re-consider environmental and allergen control measures.…”
Section: Discussionsupporting
confidence: 91%
“…Numerous studies in the United States have demonstrated the association between both mouse and cockroach allergen exposure and increased asthma morbidity, including increased asthma symptoms and exacerbations, increased acute visits and hospitalizations for asthma, and lower lung function in urban children with asthma. [12][13][14][26][27][28] The above-mentioned study of Polish children with asthma found cockroach exposure to be associated with more severe asthma and lower lung function. 25 In addition to increased exposure to pest allergens, children in urban neighborhoods are also at increased risk of exposure to mold, which has also been associated with housing disrepair and low-income housing.…”
Section: Indoor Allerg En S and MI Crob E Smentioning
confidence: 98%
“…Pest allergen exposure, especially when combined with sensitization, has been repeatedly associated with asthma morbidity. Numerous studies in the United States have demonstrated the association between both mouse and cockroach allergen exposure and increased asthma morbidity, including increased asthma symptoms and exacerbations, increased acute visits and hospitalizations for asthma, and lower lung function in urban children with asthma 12–14,26–28 25 …”
Section: Indoor Allergens and Microbesmentioning
confidence: 99%
“…[61][62][63] Pest allergen exposure has been repeatedly linked to risk of asthma, asthma prevalence, morbidity, and abnormal lung function. 59,[64][65][66][67] Recent data suggest that pest allergen exposure may lead to reduced lung function growth, 68 which has implications for future risk of adult lung disease and mortality. [69][70][71][72] Similarly, poor housing quality and housing disrepair are associated with risk of exposure to mold, 73 and exposure to mold is associated with childhood wheeze and asthma prevalence and morbidity.…”
Section: Neighborhood Safetymentioning
confidence: 99%